Thermal Stability Study of Dye-Sensitized Solar Cells with Cobalt Bipyridyl–based Electrolytes. (20th September 2016) - Yang, Wenxing; Hao, Yan; Ghamgosar, Pedram; Boschloo, Gerrit
Abstract: Dye-sensitized solar cells (DSSCs) with cobalt bipyridyl–based electrolytes can display higher solar cell performance than their iodide/triiodide counterpart. There is, however, little knowledge on their long term stability, which is a crucial aspect for potential commercial application. Herein, we studied the thermal stability of DSSCs using Co(bpy)3 2+/3+ redox electrolyte at 70 °C in the dark for 50 days, combining 3 different additives, 4-tert-butylpyridine (TBP), 1-methylimidazole (MBI) and 2, 2′-bipyridyl (BPY), in a nonvolatile solvent 3-methoxypropionitrile (MPN). Significant voltage decreases were found for all the studied solar cells, with a mechanism involving both a positive shift of the conduction band edge potential of TiO2 and a decreased electron lifetime, characterized by time resolved transient modulation techniques. Furthermore electrochemical impedance spectroscopy and differential pulse voltammetry studies indicate that the stability of Co(bpy)3 3+ is limited, causing an increased diffusion resistance in the electrolyte, but, surprisingly, no substantial change of the short-circuit current density ( Jsc ) in the devices. Overall, the DSSCs fabricated with the addition of both MBI and BPY in the electrolyte show the highest stability, maintaining 96% of its initial efficiency after 50 days, resulting from the overall compensation effects between the open circuit voltage decrease and the Jsc increase. These results provide insights about the degradation mechanism and emphasize the importance of the stability of TiO2 /dye/electrolyte interface for the device stability under thermal stress.